Uptake and correlates of chlamydia and gonorrhea testing among female sex workers in Southern China: a cross-sectional study - Pei Zhen Zhao; Ya Jie Wang; Huan Huan Cheng; Ye Zhang; Wei Ming Tang; Fan Yang; Wei Zhang; Ji Yuan Zhou; Cheng Wang (BMC, 2021)
Abstract Background Female sex workers (FSW) are highly susceptible to chlamydia and gonorrhea infection. However, there is limited literature examining their testing uptake to date. This study aimed to assess the uptake and determinants of chlamydia and gonorrhea testing among FSW in Southern China. Methods A cross-sectional study with convenience sampling was performed in five cities in Southern China. Data on socio-demographic characteristics, sexual behaviors, chlamydia and gonorrhea testing, and the utilization of health care services from participants were collected through face-to-face interviews. Univariate and multivariable logistic regressions were used to determine factors associated with chlamydia and gonorrhea testing, respectively. Results Overall, 1207 FSWs were recruited, with the mean age of 30.7 ± 6.8 years and an average number of clients of 7.0 (4.0-10.0) per week. 65.4% participants constantly used condoms with clients during the past month. Only 7.5 and 10.4% had been tested for chlamydia and gonorrhea in the last year, respectively. Multivariable analysis indicated that FSW who worked at low tiers (adjusted Odds Ratio (aOR) = 2.36, 95%CI:1.23-10.14), had more clients in the last month (aOR = 1.03, 95%CI:1.01-1.05), used condoms consistently (aOR = 1.79, 95%CI:1.12-2.86), had STD symptoms (aOR = 4.09,95%CI:2.62-6.40), had been tested for HIV (aOR = 5.16, 95%CI:3.21-8.30) or syphilis (aOR = 6.90, 95%CI:4.21-11.22) in the last year were more likely to have chlamydia testing. In addition, FSW who had more clients in the past month (aOR = 1.02,95%CI:1.00-1.04), had STD symptoms (aOR = 3.33, 95%CI:2.03-5.46), had been tested for HIV (aOR = 3.94, 95%CI:2.34-6.65) and syphilis (aOR = 3.27, 95%CI:1.96-5.46) in the last year were more likely to have gonorrhea testing. Conclusions The testing rates of chlamydia and gonorrhea are low among Chinese FSW. Integrating chlamydia and gonorrhea testing into HIV testing promotion programs may help bridge the gap among FSW.